PENANGANAN TERHADAP PENGEMIS DAN GELANDANGAN UNTUK MEWUJUDKAN KESEJAHTERAAN SOSIAL DAN PENEGAKAN HUKUM DI KOTA SEMARANG - Abdul Kholiq; Sunarto Sunarto (Jurnal Hukum Mimbar Justitia, 2022)
Beggars and homeless people are classified as a social disease which is a social problem that must be addressed immediately, this is a violation of the law as stipulated in Article 504 of the Criminal Code and Article 505 of the Criminal Code. Efforts to deal with it are usually only like controlling and social rehabilitation who are returned to their place of origin or their family, after being equipped with skills, while the imposition of criminal sanctions by the article mentioned above has not been implemented, because this is also related to Article 34 paragraph 1 of the 1945 Constitution which reads: "Fakir the poor and neglected children are cared for by the Stateâ€, so the handling is to tend to let beggars and homeless people. Based on the description above, the problem arises of how to deal with beggars and homeless people related to Article 34 (1) of the 1945 Constitution. The method used in writing this paper is normative juridical, that is, an approach based on the main legal material by examining theories, concepts, legal principles, and literature as well as applicable laws and regulations, especially the Book of Laws. the Criminal Law (KUHP), Article 504 and Article 505, and the 1945 Constitution, Article 34 paragraph (1), as well as other laws and regulations related to this research. Therefore the handling of beggars and homeless people is only controlling and social rehabilitation which is controlling and social rehabilitation of those who are returned to their place of origin or their families after being equipped with skills, while the prosecution of beggars and homeless people as stipulated in Article 504 of the Criminal Code and Article 505 of the KHUP has not been implemented.Keywords: Beggars, homeless people, Article 34 paragraph (1) of the 1945 Constitution.